STUDENTS’ PERCEPTION TOWARDS UNTILIZING SHOW AND TELL IN IN LEARNING SPEAKING - Novandy Adhitya; Devi Mivtahuljanah (English Education Department of STKIP Pasundan, 2022)
This study was aimed to find out the students’ problems and perception towards utilizing show and tell in speaking activity. This study was analyzed qualitatively to collect the data and answer the research questions that guided this research. This research was conducted for second grade students who were previously in first grade even semester who had studied English using show and tell method in one of vocational high school in Cimahi. The instruments of this study were obtained by giving the questionnaire and interviews to students. The data was obtained through google form and interview transcripts. Based on the questionnaire and interview, it was discovered that some problems exist. They often stammer when speaking or explaining using English, feeling passive in English learning activities, and lack of understanding of English vocabulary. However, the students’ perceptions were positive. It could be seen from the data of students’ perceptions on questionnaire and interview session. From the research, a conclusion can be made, that utilizing show and tell method has generated positive perceptions in the speaking activity for second grade in one of vocational high schools in Cimahi.